Semantic Field of Stres and Depression on Psychologycal Korean Drama - Adnin Kamil Bani Hawa; Nur Alifah Septiani; Yucha Febria Kusumaningrum (JETLi: Journal of English Teaching and Linguistics, 2021)
Korean dramas with the psychological genre are very popular nowadays. Through this psychological Korean drama genre, people begin to get to know some psychological terms, such as stress and depression. Unfortunately, there are many people who have not been able to interpret these two terms correctly.  The aims of this study are to find out how the words stress and depressions influence the audience of psychological Korean dramas and to know the difference of semantic field between the word stress and depression. The method used in this study is a qualitative descriptive method. The steps taken are (1) data collection with interviews, surveys through questionnaires, and readings text in psychological Korean dramas genre; (2) see the relevance between the data available and the semantic field theory; (3) and draw conclusions from the results of the research. This study uses semantic studies by looking at semantic field of the words stress and depression in psychological Korean dramas and how these words influence the audience. The semantic field is part of semantic system which is looking at the meaning of lexical elements that relate to spoken language used in reality. The subject of this study is a psychology Korean drama and psychology Korean drama audience. The results of this study showed that some respondents who watched the Korean drama misinterpret the meaning of stress and depression. Semantic field of the term stress and depression is set semantic field. Set semantic field refers to paradigmatic relationships because words or elements are in the same set and can replace each other. These two words are still in the same set, namely psychic problems. The writers hoped that it can reduce public misunderstanding of the meaning of the words stress and depression